Sublime: an aesthetic element in Art - Gurung, Man Bahadur (Journal of Fine Arts Campus, 2025)
Sublime is an aesthetic element widely incorporated in art. The element arouses an aesthetic experience, mixed with both fear and awe. The concept of the sublime as an aesthetic element was primarily brought forward by Edmund Burke and Immanuel Kant in the 18th century. Its presence in art has remained visible throughout history. The aesthetic experience of the sublime in art is present in the ancient cave paintings and Egyptian artifacts. They are found in the artworks of the Medieval and Renaissance periods. The Romanticists ventured into the wilderness to experience sublimity to express it in their artworks. The Abstract Expressionists took the idea of the sublime and made it their principal objective in art creation. Today, the sublime has become an essential aesthetic element in art. This research article, based on a qualitative research method, aims to explore the aesthetic application of the sublime in art, relying on both primary and secondary sources of data.